2020
DOI: 10.19111/bulletinofmre.726391
|View full text |Cite
|
Sign up to set email alerts
|

Integration of the GNSS method and borehole camera to model the resulting spherical cavity generated by the main charge blast in clay

Abstract: Integration of the GNSS method and borehole camera to model the resulting spherical cavity generated by the main charge blast in clay

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Experimental blasting has determined the effective ranges of explosive charge masses of Permonex V19 and Pakaex which achieved spherical expansion in clay soil. It has been found that spherical expansion for a given borehole diameter of 131 mm and a borehole depth of 2.00-3.00 m can be achieved by explosive charge of Permonex V19 and Pakaex, ranging from 0.2 to 1.6 kg [2,5]. The most significant result was certainly the determination of the volume of the resulting expansions in the clay soil during the blasting of a series of boreholes placed on a certain profile (Figure 2).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental blasting has determined the effective ranges of explosive charge masses of Permonex V19 and Pakaex which achieved spherical expansion in clay soil. It has been found that spherical expansion for a given borehole diameter of 131 mm and a borehole depth of 2.00-3.00 m can be achieved by explosive charge of Permonex V19 and Pakaex, ranging from 0.2 to 1.6 kg [2,5]. The most significant result was certainly the determination of the volume of the resulting expansions in the clay soil during the blasting of a series of boreholes placed on a certain profile (Figure 2).…”
Section: Introductionmentioning
confidence: 99%
“…The most significant result was certainly the determination of the volume of the resulting expansions in the clay soil during the blasting of a series of boreholes placed on a certain profile (Figure 2). To calculate the resulting expansion volume, the application "Bušotine" was designed [2,5]. In addition to the application calculating the resulting expansion, it draws 2D and 3D models of it (Figure 3).…”
Section: Introductionmentioning
confidence: 99%